Explosion hazards in the process industries - Eckhoff, Rolf K. (Gulf Professional Publishing is an imprint of Elsevier, 2016)
Explosion Hazards in the Process Industries, Second Edition, delivers the most current and comprehensive content for today's process engineer. Process safety and petrochemical engineers inherently accept that there is a risk of explosions when working on process facilities such as plants and refineries. Yet many that enter this field do not have a fundamental starting point to understand the nature of explosions, and there are a lot of misconceptions and impartial information in the market. Explosion Hazards in the Process Industries, Second Edition, answers this need by providing engineers and consultants a go-to reference and training guide to understand the principles of explosions, what causes them, and how to mitigate and prevent them from reoccurring. Enhanced to include new chapters on BLEVE (Boiling Liquid Expanding Vapor Explosions), water vapor explosions, and destructive effects from accidental explosions, this guide continues to fulfill a comprehensive introduction to the subject, rounded out with new case studies, references, and a discussion on methods of hazard and risk analysis
Includes bibliographical references and index
Keywords: Explosions; Explosives / Safety measures; Hazardous substances / Accidents / Prevention; Explosives -- Safety measures; Hazardous substances -- Accidents -- Prevention; Explosions -- Case studies; Fallstudiensammlung